If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19(2a + -3b + 8c) = 0 (2a * -19 + -3b * -19 + 8c * -19) = 0 (-38a + 57b + -152c) = 0 Solving -38a + 57b + -152c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-57b' to each side of the equation. -38a + 57b + -57b + -152c = 0 + -57b Combine like terms: 57b + -57b = 0 -38a + 0 + -152c = 0 + -57b -38a + -152c = 0 + -57b Remove the zero: -38a + -152c = -57b Add '152c' to each side of the equation. -38a + -152c + 152c = -57b + 152c Combine like terms: -152c + 152c = 0 -38a + 0 = -57b + 152c -38a = -57b + 152c Divide each side by '-38'. a = 1.5b + -4c Simplifying a = 1.5b + -4c
| 13x-2(4x-5)=66-3x | | 5z^2-37zy+42y^2=0 | | 72+24w=288 | | 3(4x-3)= | | 2ln(x)=4 | | 24+16p=4p | | 24x-32=24x+36 | | 5+2j=27 | | 50-82d-86-8d+7+4d= | | -5x+(2+x)= | | 5+2j=25 | | 6w^3y^6-3u^3w^2/6w^5 | | y=(2x+5)2 | | 27=5+2j | | q=p-30 | | -4.8(x+3)+6.5(x-1.2)=-25.09 | | 19+n=42 | | -4y+3x=28 | | 15+4n=63 | | 6x*7y= | | (a^-2b/ab^6)^-3 | | -5+9=a+5-7 | | X-53=27 | | 4b=80 | | 0.06=n(7) | | 11a=77 | | 8x+8=4x+2 | | 10-1/3n= | | 5v^2-10v-175=0 | | 20+20+20=60 | | -2+.25n= | | .35x+.5y=13.45 |